Internet of Things Based Automatic Visitor Counter - Afriani, Dina; Ilham, Dirja Nur; Khairuman; Talib, Mohammed Saad; Harahap, Muhammad Khoiruddin (Information Technology and Science (ITScience), 2022)
In modern times, there are many recreational areas including, Gunung Lampu Tapaktuan Tourism. This destination is very crowded with local and foreign tourists. This study aims to determine the number of visitors, optimize the place, evaluate the area's attractiveness, and know how the tool works using the experimental method. Furthermore, the Internet of Things (IoT) connects physical objects with electronics, software, sensors, and networks that make these objects collect and transmit data. From the results of the trials that have been carried out, every passing visitor is read by an ultrasonic sensor and then sent to the Thingspeak server using the internet network and the registered apikey. The ultrasonic sensor sends data that has been read to the thing peak channel that is connected to the device so that the results of the monitoring are the number of visitors in the form of graphs and tables. The results of testing the tool for seven days contained a total of 1,596 manual data, 1,582 people were detected, and 14 people were not detected. While visitors came out there were 1,559 people caught, and 37 people were not seen. From the seven days of testing, 99.12% of incoming visitors were detected and 97.68% of outgoing visitors were detected. So that it can be concluded, that this tool has been functioning correctly.